HEPATOPROTECTIVE ROLE OF LOVASTATIN - PREGNANE X RECEPTOR AGONIST IN LITHOCHOLIC ACID INDUCED LIVER CHOLESTASIS DISEASED RATS - Nain, Parminder; Dhingra, Mohit; Nain, Jaspreet (Journal of Biomedical and Pharmaceutical Research, 2019)
Objective: Pregnane X receptor (PXR), member of nuclear receptor family, an integral component of the body defence mechanism against chemical insult are expressed in the liver, gastrointestinal system & lungs. Some studies have shown that the lovastatin is pregnane X receptor (PXR) activation effect.Methods: In the present study the hepatoprotective effect of lovastatin was investigated against lithocholic acid induced liver toxicity. Liver markers in serum and antioxidant enzymes in liver tissue were assessed by using standard procedures.Results: The level of liver marker (such as SGOT & SGPT) and bilirubin were increased significantly (p<0.05) and antioxidant enzyme (i.e. SOD, GSH and CAT) were significantly (p<0.05) decrease in lithocholic acid treated groups as compared to control group. Lovastatin at doses of 0.1, 0.2, 0.3 mg/kg showed significantly (p<0.05) decrease in the levels of liver marker (SGOT & SGPT) and bilirubin as compared to the positive control group in both pre & post treated models. The antioxidant enzymes such as Superoxide dismutase (SOD), Glutathione (GSH) and Catalase (CAT) content in liver tissue were significantly (p<0.05) increase after administration of lovastatin at dose dependent manner in both pre & post treated models.Conclusions: The results of the present study indicates that under the present experimental conditions, lovastatin showed hepatoprotective abilities against lithocholic acid induced hepatotoxicity in albino rat.Keywords: Hepatoprotection, lovastatin, Lithocholic Acid, Pregnane X Receptor